Karakteristik Pupuk Organik Dari Pengolahan Limbah Peternakan Sapi Potong Di Kelompok Ternak Banteng Tani Di Kecamatan Losarang Kabupaten Indramayu - Dadat Mashudi; Oki Imanudin; Aaf Falahudin (Tropical Livestock Science Journal, 2023)
This research was conducted at the Banteng Tani Livestock Group, Losarang District, Indramayu Regency from February 20 to March 30, 2022. This study aims to analyze the quality of solid organic fertilizer (organic fertilizer) and liquid organic fertilizer (POC) from beef cattle farm waste in the livestock group. Banteng Farmer, Losarang District. This study uses a descriptive field experiment method, the observed variables are physical characteristics of organic fertilizers (color, texture, pH and temperature) and chemical characteristics of organic fertilizers including N, P and K content from 2 treatments on organic fertilizers without added EM-4. (P1) with organic fertilizer with the addition of EM-4 (P2). The results showed that solid organic fertilizer (P2) had physical characteristics in the form of a blackish color, crumb texture and an earthy smell, in contrast to P1 with a brownish color with a slightly crumbly texture and a slight smell of feces. Similarly, the chemical content in P2 contains N 0.94%, P 0.37% and K 0.55%, this is higher than (P1) with N content 0.61%, P 0.26% and K 0 ,48%. For liquid organic fertilizer, P2 contains N 0.57%, P 0.62% and K 1.23% higher than P1 with N 0.27%, P 0.41% and K 1.06%. Processing of beef cattle farm waste at the Banteng Tani Farmers Group using EM-4 (P2) can improve the characteristics and improve the quality of solid organic fertilizers and liquid organic fertilizers compared to those without added EM-4 (P1) and have met SNI compost standards.